Different preferences of IVF and SCNT bovine embryos for culture media. Issue 1 (February 2014) - Xiong, Xian-rong; Wang, Li-jun; Wang, Yong-sheng; Hua, Song; Zi, Xiang-dong; Zhang, Yong
Summary The preference of fertilized (IVF) and somatic cell nuclear transfer (SCNT) presumptive zygotes for different media when cultured in vitro to the blastocyst stage was evaluated in this study. The experiment comprised two zygote production methods (IVF and SCNT) × two culture media (mSOF and G1.5/G2.5) factorial design in which culture droplets that contained approximate 30 presumptive zygotes formed the experimental plots for the assessment of cleavage and blastocyst development. There were 15 to 20 replicates (culture droplets) per treatment combination. Sub-samples 30 to 41 of the blastocysts produced were assessed for cell number and cell apoptosis. A further 10 blastocysts per treatment combination were used for quantitative real-time polymerase chain reaction (RT-PCR) to evaluate the relative abundance of Hsp70 and Bax mRNA. Presumptive zygotes produced by IVF were developmentally more competent than SCNT zygotes in terms of cleavage rate (66.9 vs. 57.0%; P < 0.05) and blastocyst development rates (blastocysts of presumptive zygotes 29.7 vs. 24.8%; blastocysts of cleaved zygotes 44.4 vs. 36.6%; P < 0.05). Over both zygote production systems, however, the results were similar whether culture was in mSOF or in G1.5/G2.5 media for cleavage rate (63.2 vs. 62.4%; P > 0.05) and blastocyst development rate (blastocysts of presumptive zygotes 26.4 vs. 25.7%; P > 0.05; blastocysts of cleaved zygotes 41.8 vs. 41.2%; P > 0.05). There was, however, a significant interaction between the method of zygote production and culture medium for the apoptotic index of blastocysts. The interaction was such that IVF-produced zygotes cultured in mSOF had a lower apoptotic index compared with those cultured in G1.5/G2.5 (4.7 ± 1.2% vs. 9.8 ± 0.9%; P < 0.05) whereas SCNT zygotes had a higher apoptotic index when cultured in mSOF compared with those cultured in G1.5/G2.5 (11.9 ± 1.5% vs. 4.5 ± 1.2%; P < 0.05). Moreover, RT-PCR analysis showed that embryos from IVF-produced zygotes cultured in mSOF had a lower expression level of stress-related and apoptosis genes (Hsp70 and Bax) than those cells cultured in G1.5/G2.5 medium, while SCNT-derived embryos cultured in mSOF had a higher expression level of these genes than those embryos cultured in G1.5/G2.5 medium. The results of this study show that bovine IVF- and SCNT-produced presumptive zygotes have different nutrient requirements for in vitro culture to the blastocyst stage of development. IVF-derived zygotes have a preference for mSOF as the culture medium whereas the G1.5/G2.5 medium is more suitable for the culture of bovine SCNT-derived zygotes.